PENDUGAAN PARAMETER GENETIK DAN KOMPONEN RAGAM KAMBING KACANG ESTIMATION OF GENETIC PARAMETERS AND COMPONENTS OF VARIANCE KACANG GOATS - Muhammad Ary Syahputra (Universitas Sumatera Utara, 2016)
ABSTRACT This research aimed to estimate value of genetic parameters and components variance of kacang goats. This research was conducted in goat center Sei Putih, Medan. In June - August 2015. The research material consists kacang goat production records for one generation as much as 20 goats (9 males and 11 female). The variables measured are birth weight, weight of 3, 6, 9 and 12 month. Heritability and genetic correlations were estimated using a nested design unbalanced and breeding value was calculated using the single measurement it self.The results showed that the coefficient variance of birth weight, 3,6, 9 and 12 month were 33%; 26%; 21%; 26% and 30%, respectively. Heritability of birth weight, weight 3,6 month were 0,05; 0,03; and 0,04,respectively. Genetic correlation value birth weight - weight at 3; 6; 9 and 12 month (0,55%; 0,34%; 0,28%; 0,25%), weight 3 – weight at 6; 9 and 12 month (0,41%; 0,54%; 0,56%), weight 6 – weight at 9 and 12 month (0,84%; 0,64%) , weight 9 - weight at 12 month (0,83%). The conclusion of the study are coefficient variance of growth traits categorized high, but heritability is low and genetic correlation is moderate to high category. Keywords : Kacang goats, genetic parameters, components of variance ABSTRAK Penelitian ini bertujuan untuk mengestimasi nilai parameter genetik dan komponen ragam pada kambing Kacang. Penelitian ini dilaksanakan diBalai Penelitian Kambing Potong Sei Putih, Galang pada bulan Juni 2015 sampai Agustus 2015. Materi penelitian terdiri dari catatan produksi kambing Kacang selama satu generasi sebanyak 20 ekor (9 ekor pejantan dan 11 ekor betina).Variabel yang diamati adalah bobot lahir, bobot 3, 6, 9 dan 12 bulan. Heritabilitas dan korelasi genetik diestimasi menggunakan pola tersarang (Nested disegn) model unbalanced dan nilai pemuliaan dihitung menggunakan pengukuran tunggal dirinya sendiri. Hasil penelitian menunjukkan bahwa nilai koefisien keragaman dari sifat bobot lahir, 3, 6, 9 dan 12 bulan berturut – turut-adalah 33%; 26%; 21%; 26% dan 30%. Nilai heritabilitas sifat bobot lahir,3 dan 6 bulan berturut – turut adalah 0,05; 0,03 dan 0,04. Nilai korelasi genetik bobot lahir – bobot 3,6 dan 12 bulan (0,55%; 0,34%; 0,28%; 0,25%), bobot 3 bulan - 6, 9 dan 12 bulan (0,41%; 0,54%; 0,56%), bobot 6 – 9 dan 12 bulan (0,84%; 0,64%) dan bobot 9 – 12 bulan (0,83%). Kesimpulan dari penelitian ini menunjukkan nilai koefisien keragaman yang tinggi, nilai heritabilitas termasuk kategori rendah dan nilai korelasi genetik termasuk kategori sedang – tinggi. Kata kunci : Kambing Kacang, parameter genetik, komponen ragam